2019
DOI: 10.1155/2019/2107821
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directives of German People with Parkinson’s Disease Are Unspecific in regard to Typical Complications

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative movement disorder with an increased morbidity and mortality. People with PD (PwP) may suffer from decreased quality of life due to various motor and nonmotor symptoms. To a huge proportion, PwP have written an advance directive (AD); however, the content of these forms in regard to PD-specific complications is unclear. The aim of this study was to qualitatively and quantitatively analyze ADs of PwP in Germany. ADs of PwP were analyzed in a German samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Our previous study has shown that the majority of PwP have a well-prepared AD in terms of general end-of-life aspects. However, the AD hardly deals with the possibilities of specific PD therapy [13]. To our knowledge, this is the first study aiming at improving the specificity of ADs of PwP by developing 14 PD-specific recommendations to be integrated into ADs of PwP as well as to be used as instructions for attending physicians.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study has shown that the majority of PwP have a well-prepared AD in terms of general end-of-life aspects. However, the AD hardly deals with the possibilities of specific PD therapy [13]. To our knowledge, this is the first study aiming at improving the specificity of ADs of PwP by developing 14 PD-specific recommendations to be integrated into ADs of PwP as well as to be used as instructions for attending physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the AD is a legally binding document that comes into force when the patient is no longer able to express their own will. To be legally valid in clinical situations, the content of an AD has to be highly specific [13]. In Germany, ADs and determination of a health care proxy are two different legal documents.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations